Logic and its applications : 7th Indian Conference, ICLA 2017, Kanpur, India, January 5-7, 2017, Proceedings /: 7th Indian Conference, ICLA 2017, Kanpur, India, January 5-7, 2017, Proceedings. (2017) - Unknown
No abstract available